Efektivitas Metode Demonstrasi dalam Menarik dan Meningkatkan Minat Belajar Alkitab bagi Anak Sekolah Minggu Gereja Toraja Jemaat Een Haezer Benteng Pampang - Osmianty Osmianty; Juliati Juliati; Apriana Apriana; Dewi Mangolo; Karmita Sambo Datu (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research is library research or research using library methods. The technique used in collecting data is to use sources originating from books, journals that are related to Sunday school and demonstration methods. This research aims to equip and equip Sunday school teachers in increasing Sunday school children's interest in learning, especially in teaching Christianity.